(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, the knowledge and technology in the nanotechnology domain are quickly developing and research, industrial, and service centers require more efficient instruments for the identification of the nanomaterial. Recently, some deviations have been observed within patterns and samples which make us understand that the more nanotechnology science will be developed, the more physical phenomena would be prominent and visible. In other words, the more we approach small and smaller scales, i.e. nano dimensions, new pieces of physical knowledge will be developed. These developments can be applied for future technological achievements. Nanotechnology developments are a matter of measurement, development, fabrication, and manipulation of individual structures on a nanometer scale. All these procedures have been made possible only through the development of scanning probes, optical tweezers, electron microscopy with high dissociation power and lithographic tools, focused ion beam milling system, and many other tools. An important category of tools in material identification is spectrophotometers or spectrometers. Accordingly, various kinds of spectrometers have been investigated in this study and a spectrometer for nanoparticles’ scattering has been developed and fabricated. The wide range of applications of visible optical instruments made the authors of this study limit their efforts to visible range spectroscopy. The research and experiment results conducted on the newly-manufactured instrument have been compared with those from commercially available spectrometers.